Finch House - Burch, Ciera (New York : Margaret K. McElderry Books, 2023)
When eleven-year-old Micah's grandfather goes missing, her instincts lead her to the off-limits Finch House, but when a boy named Theo invites her in, Micah realizes she cannot leave and must convince the house to let her go.
Keywords: Haunted houses--Fiction.; Grandparent and child--Fiction.; Friendship--Fiction.